School Administrators and Generation Z Students' Perspectives for a Better Educational Setting - Çetin, Münevver; Halisdemir, Meral (Journal of education and training studies, 2019)
The purpose of this study is to examine the school administrators and Generation Z's perspectives towards each other. The conflict between school administrators and the emerging generation has always been a hot-debate research topic, and it is undeniable that each generation with new defining characteristics make this subject to be worthwhile to re-consider and re-discuss. For this research, from various schools in Istanbul, Kadikoy province, 15 different school administrators and 20 different students of Z generation which were born 2000 and after were volunteered to participate to the research group. This study employed phenomenology pattern and semi- structured negotiation for data collection, and the analysis of the data has been done by using NVIVO 10 program. The study revealed that there are numerous factors that affect the school administrator's lives: new demands and challenges emerging with new generation, the adaptation problem to the modern instructional technologies and computer-aided teaching system, the role ambiguity, parent's approach and outside relations influence quality and school management adversely. On the other hand, the analysis of Generation Z student's perspective brings up a new perspective to the issue of generation gap. From their perspective, the school administrators fail to act in accordance with the changing time and its demands. Most important of all, the generation gap causes the problem of communication, empathy and identification, and this has a decisive, particularly negative influence on their perspective of school life and school administrators. In this study, expectations, responses and critical insights are examined from the lenses of school administrators and students in a way to provide recommendations that could be remedy for the concerns of the school administrators and Generation Z students not only in theory but also in practice.